Analyzing the Criticality of Service Level in Cab Aggregating Industry on Customer Expectations, Satisfaction, and Retention - Malik, Garima; Bansal, Sanjeev (Indian Journal of Computer Science, 2017)
All well reputed organizations know that the key to success lies in their customers. Hence in today’s world, the companies that do not provide value to their customers bring an opportunity for the competitors to jump in and steal these customers. Organization are increasingly focusing on building long-term relationship with customer, thereby increasing their probability for success by offering customers higher levels of satisfaction, increasing customer loyalty and ultimately retaining customer. Thus, the paper attempts to establish concrete relationships between service quality, customer satisfaction and customer retention. The relationship is supported through testing of hypothesis through and one sample t-test for finding out the impact of service quality and to find out the gaps in service quality of cab aggregators in consumer minds. The paper suggests certain service recovery strategies to cab aggregators which will help them reduce the gaps and enhance customer loyalty.